Traditional use of medicinal plants by elderly - Alexandre Rocha Alves Pereira; Ana Paula Machado Velho; Diógenes Aparício Garcia Cortez; Laura Ligiana Dias Szerwieski; Lucia Elaine Ranieri Cortez (Rev Rene)
Objective: identify the traditional use of medicinal plants by the elderly. Methods: exploratory and descriptive study conducted in the Intermunicipal Consortium on Health. Three hundred and fifty-one questionnaires were applied to the elderly to survey socio-demographic information and issues related to plants. Results: the use of plants was reported by 78.4% of the elderly, and these were collected in backyards. The most often cited plants were mint, boldo, fennel, lemongrass and chamomile. Regarding the reason for use, 33.3% participants said that “it’s not harmful to health”, 61.8% usually indicate the use to other people. Most elderly make use of plants in a safe manner, and these are present in the daily lives of these people as a therapeutic method. Conclusion: the elderly make use of medicinal plants as an important therapeutic resource.